Determinant of consumer attitude towards online purchase intention of halal cosmetic: moderating effect of customers experience - Naseri, Roszi Naszariah Nasni; Wan Ibrahim, Nik Rahila; Mohd Esa, Maryam; Ahmad, Nurul Zamratul Asyikin; Azis, Siti Noraziana; Abd Azis, Rafidah (Human Resource Management Academic Research Society, 2021)
The rise of internet use in Malaysia has led to a shift in consumers’ behaviour towards online purchasing, particularly the increasing trend observed in purchasing Halal cosmetic products. However, online shopping in Malaysia is constantly evolving and less familiar among consumers. Therefore, this study aims to examine the factors that influence consumer attitudes and their impact on the online purchase intention of Halal cosmetic products. This study utilises a cross-sectional data methodology and survey instrument for quantitative data collection. Responses from 400 consumers who have shopped online for a minimum of 6 months were derived. The EFA and pooled-CFA analyses were performed using IBM SPSS version 25.0 and AMOS Version 25, respectively. From the pooled-CFA measurement model, it was shown that web design, trust, perceived ease of use, as well as privacy and security had a significant and positive effect on consumer attitude, while consumer attitude and web design displayed a significant and positive relationship towards purchase intention.